Susceptibility and damage cereals to infestation Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) in storage - Hendrival Hendrival; Dhea Afriani; Dewi Sartika Aryani (Jurnal Agro, 2019)
Rhyzopertha dominica is a primary pest which causes damages to stored cereals such as corn, grain, rice, wheat, sorghum, tubers, and starch-containing substrates and packaging made from wood.  They not only cause losses in terms of quantity but also affect quality during storage period through their feeding activities.  The aimed of this research to investigate the level of susceptibility and damage to cereals during the storage period by pest R. dominica. The cereals used in the study were sorghum, wheat, corn, rice grain, white rice, black glutinous rice, and white glutinous rice. The method used in this research was no-choice bioassay with variables observed: number of F1 progeny, median development time and damage cereals. The results revealed that that different kind of cereals had a different level of susceptibility to infestation by R. dominica from moderate to susceptible. Sorghum, corn, rice, white rice, and white glutinous rice were classified as moderate, while wheat was classified as susceptible and black glutinous rice was moderate–susceptible. The highest losses were found in wheat, black glutinous rice, corn, and rice grain while the lowest were found in sorghum, white rice and white glutinous rice. The study showed that cereals that were susceptible may not stored for a long time to minimize the loss of grain weight.ABSTRAK Rhyzopertha dominica tergolong hama primer yang merusak serealia seperti jagung, gabah, beras, gandum, sorgum, umbi, dan substrat mengandung pati serta kemasan yang terbuat dari kayu. Kerusakan serealia selama penyimpanan meliputi kerusakan kuantitas dan kualitas yang disebabkan oleh hama R. dominica. Penelitian bertujuan untuk mengetahui tingkat kerentanan dan kerusakan serealia selama penyimpanan oleh hama R. dominica. Jenis serealia yang digunakan dalam penelitian terdiri dari sorgum, gandum, jagung, gabah, beras putih, beras ketan hitam, dan beras ketan putih. Metode uji tanpa pilihan dengan variabel yang diamati yaitu jumlah F1, median waktu perkembangan, dan kerusakan serealia.  Hasil penelitian menunjukkan bahwa jenis serealia memiliki tingkat kerentanan dari moderat sampai rentan terhadap infestasi hama R. dominica. Serealia dari sorgum, jagung, padi, beras putih, dan beras ketan putih tergolong dalam kategori moderat, sedangkan gandum tergolong dalam kategori rentan, serta beras ketan hitam tergolong moderat–rentan terhadap serangan R. dominica. Tingkat kerusakan serealia seperti persentase serealia berlubang dan persentase bubuk serealia paling tinggi terjadi pada gandum, beras ketan hitam, jagung dan padi sedangkan kerusakan yang terendah yaitu pada sorgum, beras putih, dan beras ketan putih. Penelitian menunjukkan bahwa serealia yang rentan tidak boleh disimpan dalam waktu yang lama untuk meminimalkan kehilangan berat.